Strategi Badan Perencannan Pembangunan Daerah Dalam Merencanakan Pembangunan Di Kabupaten Bone - Maulani, Andi Magfira; Ansyari, Muh Isa; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2020)
This study aimed to find out the Strategy of the Regional Development Planning in Bone Regency and to know the supporting and inhibiting factors in the process of the regional development planning strategy. Data collection techniques used observation, interview with 4 informants and documentation . Data analysis used interactive analysis models and 3 types of triangulation in data validation. The results of this study showed that the strategy in planning development had been carried out optimally, this was seen from the perspective of organizational policy the ability could describe the strategy , Employee Motivation could work productively based on their ability, but in terms of the location of resources still not run well because of insufficient material resources. Supporting factors in this planning strategy were (a) Organizational Policy and Development Policy, and (b) Potential and Productivity. Then the inhibiting factors were (a) HR Empowerment and (b) Material Resources.